2022
DOI: 10.1152/ajpheart.00218.2022
|View full text |Cite
|
Sign up to set email alerts
|

Taking to “heart” the proposed legislation for permanent daylight saving time

Abstract: In March 2022, the United States Senate passed the Sunshine Protection Act that would abolish the biannual change in clocks each fall and spring, and permanently adopt daylight saving time that aligns with the 'spring forward' time change each March. A number of scientific and medical societies have endorsed the abolishment of the biannual clock change, but oppose the permanent adoption of daylight saving time. Instead, leading organizations such as the American Academy of Sleep Medicine (AASM) and the Society… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Among other points, Rubio alleged that DST transitions caused 28 fatal motor vehicle accidents, a highlight from Fritz et al (2020). Much to the dismay of authors' study and many others (Carter et al 2022;Roenneberg et al 2019), Rubio vowed for locking the clock in the DST setting -that is, making DST the new perennial Standard Time -even though the study also showed that the risks of fatal accidents doubled after DST spring transition was advanced 3 weeks in the US after the Energy Policy Act (Martín-Olalla 2020). Note that the Sunshine Protection Act of 2021 would effectively advance DST "spring transition" by 10 weeks and delay DST "autumn transition" by 8 weeks to cancel out both.…”
Section: Discussionmentioning
confidence: 99%
“…Among other points, Rubio alleged that DST transitions caused 28 fatal motor vehicle accidents, a highlight from Fritz et al (2020). Much to the dismay of authors' study and many others (Carter et al 2022;Roenneberg et al 2019), Rubio vowed for locking the clock in the DST setting -that is, making DST the new perennial Standard Time -even though the study also showed that the risks of fatal accidents doubled after DST spring transition was advanced 3 weeks in the US after the Energy Policy Act (Martín-Olalla 2020). Note that the Sunshine Protection Act of 2021 would effectively advance DST "spring transition" by 10 weeks and delay DST "autumn transition" by 8 weeks to cancel out both.…”
Section: Discussionmentioning
confidence: 99%
“…This leaves jurisdictions with the need to decide on which permanent time to adopt. Although most jurisdictions are considering pDST, sleep and circadian experts generally [15 ▪ ,37 ▪ ,38,39], but not exclusively [40] advocate for pST. The advocacy for pST emerges from an understanding that the circadian system requires natural sunlight to set its phase [41].…”
Section: Introductionmentioning
confidence: 99%